Characterization and Treatment Pharmaceutical Wastewater by Photo-Fenton Process - Endang Kusumawati; Bunga Liswandila; Erisca Saputri; Tifa Paramitha (Universitas Muhammadiyah Purwokerto, 2025)
The characteristics of the PT X pharmaceutical wastewater influent were a pH of 7.18, a COD of 384 mg/L, and a red-brown color. The Chemical Oxygen Demand (COD) has not met the quality standards based on the Ministry of Environment and Forestry Regulation No. 5 of 2014. The red-brown color was caused by wastewater containing rifampicin as a component of the tuberculosis drug. The objectives of this study were treating the real pharmaceutical wastewater to reduce COD and color by varying the molar ratio of the Fenton reagents and to identify the influence of the neutralization process. The Fenton reagents were FeSO4.7H2O and H2O2 with a molar ratio of 1:1.5, 1:2, and 1:3. The process was conducted with the help of UV light and acidic conditions. The photo-Fenton process produced residues, which can be neutralized by using 0.1 NaOH solution and coagulated by using NaCl. The neutralization process successfully decreases the amount of Fe, H2O2, and COD on liquid. The results showed that the best molar ratio is 1:2, which can be seen from the removal efficiency of organic compounds of 89.58%, and the color decrease is seen from the decrease in absorbance value.